Alexander's Final Army. - Miller, Jonathan A. (Tufts Archival Research Center, 2005)
During the reigns of Philip II and his son Alexander III (the Great), the kingdom of Macedonia grew to encompass an area stretching from the Danube to the Indus, and from Egypt to Uzbekistan. This period of expansion was the product of a newly reformed Macedonian army. However, at the time of Alexander's death in 323 the army was undergoing significant changes, not only in structure but also in composition. Iranians were extensively being pulled into its ranks, despite the outcry from the Macedonian rank and file. What was it that Alexander hoped to accomplish by reforming the most powerful military of the age? To answer this question, I cross-referenced the surviving ancient histories of Alexander's campaigns with what is known about Macedonia before and during Philip's reign. As it turns out, no one paradigm defined the relationships between myriad subject peoples and the Macedonian king. Rather, numerous political structures developed, all of which linked the inhabitants of Macedonian-dominated regions to the Macedonian military, over which the Macedonian kings exercised direct control. Philip cemented these relationships into constitutionally bounded and legitimatized structures, which would form the basis upon which Alexander began building his empire in Asia. This process was far from complete when he dies in 323 BC at the age of 32. Alexander's true plans for his empire, therefore, can best be viewed from an analysis of the military changes he initiated, and where the integration of the Iranians fit within that paradigm.